Localization System for Optimization of Picking in a Manual Warehouse - Pereira, Maria Teresa (2020)
Inbound logistics assumes increasing importance in retail operations, because there are usually hidden inefficiencies that contribute to higher labour costs and more time spent in the usual procedures in warehouses. The work developed was carried out in a manual warehouse of a retail company, with the main goal being the optimization of picking tasks and the improvement of the warehouse operations, as well as stock management. The solution is based on the development and implementation of a localization system, to reduce one of the most time-consuming components of picking, the search time for products in the warehouse. This application led to a reduction of this unproductive time by 93% to 100%, meaning the complete elimination of this component, which led to an optimization of the picking activity, by increasing the warehouse preparation capacity by 63%. Apart from the software upgrade, the operators now use Personal Digital Assistants to perform and validate the picking of items, increasing the accuracy of picking and the traceability of stock.